An insight in spatial corrosion prediction - Mustaffa, Zahiraniza (Elsevier Ltd., 2012)
Recent discoveries on fluidestructure interactions between the external flows and circular cylinders placed close to the wall have added new values to the hydrodynamics of unburied offshore pipelines laid on a sea bed. The hydrodynamics of waves and/or currents introduced vortex flows surrounding the pipeline. External corrosions formed in the pipelines were assumed to be partly contributed by such fluid-structure interactions. The spatial consequences of such interactions were of interest of this study. This paper summarizes selected previous experimental and numerical works reported by literature on these discoveries. Actual field data were utilized in this study for further validation. The characteristics of corrosion orientations in the pipelines were studied comprehensively using simple statistics and results were discussed. Results adopted from the field data acknowledged well to the hypothesis from the reported literature. The updated knowledge from this fluid-structure interaction is hoped to benefit the industry and constructively incorporated into the current subsea pipeline designs.